Current Condition of the Technical – Vocational & Livelihood Education in Selected Public High Schools in Congressional District 3 of Isabela, Philippines - Alabar, Mylene T.; Cristobal, Ronald M.; Damian, Harlyn B.; Dela Cruz, Allan S.; Pinniliw, Remedios L.; Malinao , Client William M. (International Journal of Business, Law, and Education, 2025)
The rapidly evolving demand for paradigm shifts in Technical Vocational and Livelihood Education in the 21st century is one of the major concerns of the Department of Education. Thus, this study explores the current conditions, the challenges and intervention strategies of the public-school teachers of Technology and Livelihood Education, Technical Vocational Education and Technical Vocational Livelihood Teachers across Junior and Senior High School in selected schools in Local District 3 in Isabela, Philippines. The descriptive research design was used to answer stated objectives of the study. Using frequency and percentage distribution, findings revealed that school's learning facilities, linkages, teacher training, student skills development, employability, and stakeholder participation reveal a strong foundation in supporting TLE (Technology and Livelihood Education) and TVE (Technical-Vocational Education) programs.